Mechanisms guiding Polycomb activities during gene silencing in Arabidopsis thaliana - He, Chongsheng; Huang, Hai; Xu, Lin (Frontiers in Plant Science, 2013)
Polycomb group (PcG) proteins act in an evolutionarily conserved epigenetic pathway that regulates chromatin structures in plants and animals, repressing many developmentally important genes by modifying histones. PcG proteins can form at least two multiprotein complexes: Polycomb repressive complexes 1 and 2 (PRC1 and PRC2, respectively). The functions of Arabidopsis thaliana PRCs have been characterized in multiple stages of development and have diverse roles in response to environmental stimuli. Recently, the mechanism that precisely regulates Arabidopsis PcG activity was extensively studied. In this review, we summarize recent discoveries in the regulations of PcG at the three different layers: the recruitment of PRCs to specific target loci, the polyubiquitination and degradation of PRC2, and the antagonism of PRC2 activity by the Trithorax group proteins. Current knowledge indicates that the powerful activity of the PcG pathway is strictly controlled for specific silencing of target genes during plant development and in response to environmental stimuli.